GAMBARAN POLA MAKAN, AKTIVITAS FISIK DAN STATUS NUTRISI PADA REMAJA SMA DI SMA KRISTEN CITRA BANGSA DI KOTA KUPANG - Yules Dapa Merang; Yasinta Betan; Arman Rifat Lette (CHMK HEALTH JOURNAL, 2022)
The background of the author doing this research is because of the problem of nutritional status in adolescents, namely how the description of diet, physical activity and nutritional status of teenagers at Citra Bangsa Christian High School in Kupang City. Then this study aims to analyze the description of diet, physical activity, and nutritional status in Citra Bangsa Christian High School Teenagers in Kupang City. The research method conducted by the author is survey research using descriptive research methods. This research was conducted at the Citra Bangsa Christian High School in Kupang City and the informants in this study were students or writers who conducted research in collecting the data needed. The authors conducted research using interview techniques by using questionnaires to obtain answers from students regarding information about diet, physical activity, and nutritional status in adolescents systematically. From the results of research conducted by the author on the description of eating patterns, physical activity, and nutritional status in adolescents, which shows that from 140 respondents, 31 respondents (22.1%) have a high eating pattern, 99 respondents (77.7%) have a high dietary pattern. eat enough by answering questions, and 10 respondents (7.1%) have a poor diet. While in the physical activity section of 140 respondents, 46 respondents (32.9%) had a high level of physical activity, 61 respondents (43.6%) had a moderate level of activity, and 33 respondents (23.6%) had a high level of physical activity. which is lacking. And on the nutritional nutritional status of 140 respondents, 36 respondents (25.7%) had a "thin" nutritional status, 92 respondents (65.7%) had a "Normal" nutritional status, and 12 respondents (8.6%) had a nutritional status. Nutrition "Fat", while the nutritional status of obesity was not obtained. Keywords: Diet, Physical Activity, Nutritional Status